Revascularization in Lesion of Arteries of the Aortoiliac Arterial Segment. Literature Review and Clinical Examples - M. A. Chernyavsky; V. A. Neverov; N. V. Susanin; V. A. Soloviev; Yu. K. Belova; A. N. Kazantsev (Неотложная медицинская помощь)
This article reports the main issues concerning the tactics of choosing the treatment of patients with occlusive-stenotic lesions of the aortoiliac segment. The key issues of the current Russian, European and American recommendations for revascularization of the peripheral vessels are demonstrated. Attention is paid to the latest studies comparing the results of open surgery and endovascular correction methods. Clinical cases are presented that demonstrate the optimal results of the use of endovascular technologies in conditions of extensive hemodynamically significant lesions and occlusion of the iliac arteries. The conclusion was made about the high efficiency and safety of interventional management in the treatment of patients with atherosclerotic lesions of the aortoiliac segment.